TEKNOLOGI PENGOLAHAN BUAH NAGADAN DIVERSIFIKASI PRODUK OLAHANNYASEBAGAI UPAYA PENINGKATAN JIWA KEWIRAUSAHAAN DI SMK AGRI INDUSTRI - Titin Hera Widi H., Ichda Chayati, Nani Ratnaningsih, (Universitas Negeri Yogyakarta, 2011)
The community program is dedicated to: 1) give alternative ofprocessing technology of dragon fruit in SMK Agriindustri to preserve andmaintain its nutrients, 2) give alternative of product diversification ofdragon fruit, and 3) give entrepreneurship motivation by having skills toprocess dragon fruit.The programs were done in August 3rd and 4th 2010, located atSMK Agriindustri Nanggulan Kulonprogo. Oral presentation, demonstration,and practicing were used as methods while training. The programwas evaluated its inputs, processes, products, and trainee satisfactions.The evaluations showed that: 1) Dragon fruit could be processed bysugar preservation, which its products were in the range of standards. 2)Dragon fruit could be processed into 6 products, i.e. dragon fruit syrup(simple and special grade), dragon fruit extract, dragon fruit instant drink,dragon fruit jam, and dragon fruit candy. 3) The community program wassuitable with the need of trainee and it could increase the motivation oftrainee's entrepreneurship.Keywords: dragon fruit, processing technology, product diversification,entrepreneurship